Response to the Commentary of Levenson and Khilwati - Geels, Antoon (The international journal for the psychology of religion, 1999)
This response focuses on a distinction between emic and etic statements, that is, descriptions from within a certain tradition and the outside scientific analysis. Although carefully listening to informants and gathering otherrelevant information, the scholar searches for universal, nonculture bound, psychological categories. Levenson and Khilwati appear to mix up this fundamental distinction.